Alumina-to-Alumina Actively Brazed Using Cu-Ti, Cu-Zr, and Eutectic Ag-Cu-Ti Filler-Metal Alloys - Hashim, F. A.; Kadhim, M. J.; Yousif, R. H. (Basrah Journal for Engineering Sciences, 2010)
Al20rA l10l bronzing systems were produced using a one-stage actively brazed technique based on Cu-Ti, Cu-Zr, and Ag-Cu-Ti alloys. Single and double butt joints were used for micro-structural and mechanical properties studies respectively. The joints that were brazed by using Cu-Zr filler-metal alloys (2%, 4%, 6%, and 8% Zr weight percent) have shown low shear strengths at the 2rO2 interface. Higher shear strength was obtained by using Cu-Ti filler-metal alloys (2%, 4%, 6, and 8% Ti weight percent), and eutectic (Ag-26%C u-4% Ti). As judged by the phases Conned at the interface, Cu2 (AlTi)4O is more effective to wet and both alumina to alumina.